Catalytic characteristics of a sn‐1(3) regioselective lipase from Cordyceps militaris. (5th December 2018) - Park, Jun‐Young; Park, Kyung‐Min; Yoo, Yoonjung; Yu, Hyunjong; Lee, Chang Joo; Jung, Ho‐Sup; Kim, Keesung; Chang, Pahn‐Shick
Abstract : A total of 39 agricultural products were screened for natural sources of lipases with distinctive positional specificity. Based on this, Cordyceps militaris lipase (CML) was selected and subsequently purified by sequential chromatography involving anion‐exchange, hydrophobic‐interaction, and gel‐permeation columns. As a result of the overall purification procedure, a remarkable increase in the specific activity of the CML (4.733 U/mg protein) was achieved, with a yield of 2.47% (purification fold of 94.54). The purified CML has a monomeric structure with a molecular mass of approximately 62 kDa. It was further identified as a putative extracellular lipase from C. militaris by the partial sequence analysis using ESI‐Q‐TOF MS. In a kinetic study of the CML‐catalyzed hydrolysis, the values of Vmax, Km, and kcat were determined to be 4.86 μmol·min −1 ·mg −1, 0.07 mM, and 0.29 min −1, respectively. In particular, the relatively low Km value indicated that CML has a high affinity for its substrate. With regard to positional specificity, CML selectively cleaved triolein at the sn‐1 or 3 positions of glycerol backbone, releasing 1, 2(2, 3)‐diolein as the major products. Therefore, CML can be considered a distinctive biocatalyst with sn‐1(3) regioselectivity. © 2018 American Institute of Chemical Engineers Biotechnol. Prog ., 35: e2744, 2019.